2020
DOI: 10.1101/2020.09.30.320804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A time-lagged association between the gut microbiome, nestling weight and nestling survival in wild great tits

Abstract: 1. Natal body mass is a key predictor of viability and fitness in many animals. While variation in body mass and therefore viability of juveniles may be explained by genetic and environmental factors, emerging evidence points to the gut microbiota as an important factor influencing host health. The gut microbiota is known to change during development, but it remains unclear whether the microbiome predicts fitness, and if it does, at which developmental stage it affects fitness traits. 2. We collected data on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 102 publications
2
6
0
Order By: Relevance
“…In support of this hypothesis, low alpha diversity at T1 predicted greater body mass at T3 in vervets, independent of maternal parity. These results are in line with studies on birds showing an association between reduced early life alpha diversity on future weight gain [23,24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In support of this hypothesis, low alpha diversity at T1 predicted greater body mass at T3 in vervets, independent of maternal parity. These results are in line with studies on birds showing an association between reduced early life alpha diversity on future weight gain [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…In humans and rodent models, reduced alpha diversity has been associated with growth deficits [20]; however, the effects have not been consistent, with other studies finding no relationship between microbial community diversity and growth [21]. In other animals, such as birds, the effects appear more consistent and with an opposite pattern: poultry birds with experimentally-reduced alpha diversity grew faster [22], and lower diversity during early life predicts faster later-life growth among free-living birds [23,24]. Beyond community diversity, experimental rodent models of the human microbiome have identified specific taxa are causally related to infant growth.…”
mentioning
confidence: 74%
“…At the genus level, the dominant bacteria noted in this study were also identified as highly prevalent in our population (Ureaplasma, Chryseobacterium, Carnobacterium). Similar microbiome compositions were reported for great tits in several other studies (Davidson et al, 2019(Davidson et al, , 2020, but population differences may paly role to some extent (e.g., Teyssier et al (2018) reported great tit microbiomes dominated by Firmicutes and Actinobacteria, with only small prevalence of Proteobacteria; notably, their analyses were done on fledglings, contrary to our study and other cited studies which used at least 1-year old adults). Blue tit microbiomes do significantly differ from microbiomes of other bird species (e.g., Darwin's finchesdomination of Firmicutes and Actinobacteria (Loo et al, 2019); swan geese -domination of Firmicutes (Wu et al, 2018); white ibises -domination of Firmicutes (Murray et al, 2020); great bastards -domination of Firmicutes and Bacteroidetes (Liu et al, 2020)), which may reflect general differences due to different dietary niches (Waite & Taylor, 2015;Grond et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Our metadata is deposited at Dryad https://doi.org/10.5061/dryad.bk3j9kd9g (Davidson, Somers, et al, 2020). Sequence data are available in the European Nucleotide Archive under access number PRJEB42330, and ERS5506097 ‐ ERS5506338.…”
Section: Data Availability Statementmentioning
confidence: 99%